TUPROQDAGI KIMIYOVIY ELEMENTLAR HOLATINI O‘RGANISH UCHUN IZOTOPIK TAHLIL METODINI QO‘LLASH USLUBLARI - Jumamuratov, A.; Jumamuratov, M.A. (SCIENCE and SOCIETY, 2020)
One of the important tasks in soil agrochemical analysis is to determine the stockpile of fluent forms of nutrients in the soil. We used the method of isotopic analysis to determine the composition of the movable part of the nutrients in the soil and determined the levels of mobility of the elements Rubidium, Cesium, Sodium, Calcium and Barium.